SOCIAL STUDIES LEARNING MODEL IN LOCAL CLASSIC BATIK CULTURAL BASED FOR THE NATION IDENTITY REINFORCEMENT OF JUNIOR HIGH SCHOOL STUDENTS - Sariyatun, - (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
The development of social studies learning model is based on classic batik local cultural value for improving the identity of Junior High School Students in Surakarta. Generally, the research is aimed to construct social study based on classic batic local cultural value to improve nation identity through using post modernism thought that views understanding a curriculum as a praxis. Based on the construction, this research is able to empower the researcher, social studies teachers and students. In order to construct the transformative curriculum as the praxis, four elements are used richness, recursions, relations and rigor. The integration of classic batik cultural value in social studies learning is based on the combination of cooperative learning model and value clarification. Knowledge and understanding to local and national cultural values will be manifested to nation identity. This research uses research and development approaches based on three main stages introductory study, model development and model validation. The data collection uses observation as well as interview guidance and study devices evaluation sheet. Data analysis uses qualitative and quantitative techniques. The main conclusion of this research outcomes is that Social studies learning model based on the developed classic batik art and cultural values model has met the study model development principles and it has been proven to significantly improve competency and strengthen student character and identity if it is compared to conventional model